Chapter La memoria delle "anziane" maestre. Ricercare radici per costruire storie - CAGNOLATI, ANTONELLA (Studi e saggi, 2019)
This contribution focuses on the memory of older women, in the role of pupils and teachers. The starting point is the awareness of the role that the elderly person plays for younger generations, as an agent of transformation and guardian of memory. The first results of a research started in the territory of Lucera (Foggia, Italy) are provided, aimed at reconstructing the life of the school after the Second World War.